Occupational Mobility in Chile 2001-2009: Inequality of Income with Equal Opportunities? [Movilidad Ocupacional en Chile 2001-2009: ¿Desigualdad de Ingresos Con Igualdad de Oportunidades?] - Espinoza-Espinoza, V (2014)
The paper compares the regimes of intergenerational occupational mobility in Chile between 2001 and 2009. Data for the study considers published mobility tables for 2001 as well as original data for 2009 from the National Survey of Social Stratification (ENES). The analysis of mobility patterns replicates the constant fluidity model proposed by Erikson and Goldthorpe (1992), considering also special parameters for Chile as proposed by Torche (2005). His depiction of Chilean society as "unequal but fluid" is challenged by the 2009 data in two special respects: First, we find a stronger hierarchical effect and a larger sectoral barriers to mobility than previously reported. Secondly, the latter yields a less fluid mobility regime. The paper also explores the hierarchical dimension of mobility by testing a "vertical" model (RCII), which provides an adequate fit in both samples. Finally, the paper compares the vertical dimension of occupational mobility with income distribution for occupational groups. These findings open a new agenda for the study of the opportunities that Chilean society offers to its inhabitants.